We live more, but we see less: Vivimos más, pero vemos menos - Cáceres-del Carpio, Javier (2019)
There is no doubt that we live longer, that is, the world population is aging; partly thanks to advances in science and technology, and its application to medicine for the prevention, cure, and recovery of different nosological entities previously considered lethal. The world life expectancy in 1990 was 65.45 years; for the dawn of the new millennium, it increased to 67.68, for 2010 to 70.68 and for 2017 to 72.25 years of life at birth. In general terms, the world population of people over 50 almost doubled from 878 million in 1990 to 1,640 million in 2015. As is already known, the fact that the population is living longer brings with it the increase of so-called degenerative diseases, among which is age-related macular degeneration (AMD). We live longer, but we see less.